“Efecto de la nutrición translaminar en las características del racimo de banano (Musa AAA. var. Williams) en el cantón Valencia”. - Navarro Patta, Francisco Rolando (2020)
The investigation was carried out at the “San Carlos Chillovado” farm, which is located at kilometer 13 of the E30 Quevedo-Valencia road in the “El Descanso” area, north of the Los Ríos Province. With the objective of: Evaluate the effect of translaminar nutrition on banana cluster characteristics (Musa AAA Var. Williams) in the canton of Valencia. A completely random block design (DBCA) was used, consisting of 5 treatments, with 4 doses of translaminar nutrient (20 mL, 40 mL, 60 mL, 80 mL) plus their respective control detailed in table 3 and 6, with a frequency of application once every 30 days, placing the product between the pseudopeciolus and the pseudostem. For the comparison of means, the Tukey test was used (p <0.05). Among the results obtained, the following stand out: variable bunch weight was better at T3 26.30 kg; variable spine weight kg was better in T1 with 3.29 kg; variable number of hands per bunches was better on T4 7.00; variable length of the fingers of the second hand, the T3 (60 ml) was better with 26.54 cm, on the other hand, for the length of the fingers of the last hand, the T4 was better with 21.85 cm. variable number of fingers of the second hand was better on T4 19.3, on the other hand the last hand was better on T4 with 14.17; variable diameter of the finger of the second hand, T4 and T3 were better with 3.45 cm, while T2 and T0 presented the lowest means with 3.38 cm, whereas the last hand for doses was the best at T4 3.8 cm. variable ratio was better in T3 1.20; The economic analysis reflects that the marginal utility of the best treatment was in T3, with income of 10,132.8 (USD). Keywords: Translaminar, fertilize, soil, bunches, weight, costs, banana.